(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
Solid biopolymer electrolytes (SBEs) systems based on 2-hydroxyethyl cellulose (2-HEC), doped with ammonium chloride (AC) and various amounts (2-6 wt%) of ethylene carbonate (EC) as a plasticizer, were prepared using the solution casting technique. The ionic conductivity of the SBEs was analyzed using electrical impedance spectroscopy (EIS), with the sample containing 2 wt% of EC showing the highest conductivity at 3.43 × 10−4 S/cm. The physical appearance and structural properties of the SBEs were also tested. Fourier transform infrared spectroscopy (FTIR) demonstrated a vibrational spectrum of composite SBEs, confirmed through comparison with Gaussian analysis, with a peak value at 2928 cm⁻¹ indicating the C-H stretching of 2-HEC. Additionally, X-ray diffraction (XRD) revealed a broadened amorphous peak for 2-HEC and a distinct peak indicating AC crystallinity. The biodegradable properties of the SBEs were assessed through soil burial. From this, decomposition of material can be observed in natural soil to prevent long-term pollution. The hydroxyl groups in the HEC molecule facilitates enzymatic breakdown from cellulase.